Ozone biomonitoring at mountainous and lowland areas in Hungary - Villányi, Vanda (Acta Biologica Szegediensis, 2008)
Our experiment started in June, 2007. For test-plant we applied the ozone bioindicator clover (Trifolium repens NC-S and NC-R) clones. For cultivation of plants and for assessing the injuries the protocol of the ICP Vegetation (International Cooperative Programme on Effects of Air Pollution on Natural Vegetation and Crops) was used. The clover pots were located in three experimental sites. Gödöllô is in downs with moderate climate, Bugacpuszta is a lowland site with hot and dry climate while Mátraháza is a mountainous site. Besides injuries and total dry weight, the number of flowers and the leaf area index were also measured. Our results showed that the typical symptoms of ozone injury were appeared on sensitive clones on every site. The degree of injury increased gradually from June to September reaching the maximum in the middle of September. There were definite differences between the numbers of flowers: in Gödöllô and Bugac (where the ozone pollution was substantially lower) the plants developed much more flowers than in Mátraháza. Therefore the number of flowers could also be a useful indicator of tropospheric ozone in addition to the extent of ozone injuries.